Genomic structural equation modeling reveals the shared genetic architecture of osteosarcopenia across five musculoskeletal phenotypes - Weiqiang Lai; Kaiqin Gong; Ronghao Zhong; Weicong Yin; Xu Li; Xinhuang He; Siyuan Hu; Chuqun Chen; Kunrui He; Chunhan Sun; Jianping Zheng; Guowei Zeng (Mammalian Genome, 2026)

Combined berberine and glycyrrhetinic acid treatment confers antiviral and host-protective effects against CAPRV2023 infection in golden pompano (Trachinotus anak) - Weicong Li; Heng Sun; Haoyu Wang; Zhiyuan Huang; Deqi Wu; Haiqing Li; Liqun Wang; Yucong Huang (Fish & Shellfish Immunology, 2026)

Evaluation of the immunological efficacy of EsxA subunit vaccine and DNA vaccine against Streptococcus iniae in golden pompano (Trachinotus anak) - Zhiyuan Huang; Heng Sun; Haoyu Wang; Xinlei Jia; Han Li; Dogbey Rejoice Abla; Weicong Li; Liqun Wang; Yishan Lu; Yucong Huang (Fish & Shellfish Immunology, 2026)

Stage-specific transcriptomic analysis reveals progressive immune activation, imbalance and escape during rhabdovirus infection in golden pompano (Trachinotus anak) - Yucong Huang; Heng Sun; Haoyu Wang; Wenjie Zheng; Xiaojuan Li; Deqi Wu; Weicong Li; Haiqing Li; Jia Cai; Liqun Wang (Aquaculture, 2026)

Enhanced nitrogen removal and mitigated greenhouse gas emissions in bioelectrochemical system-modular moving bed wetland at low temperature: Functional zonation and multi-pathway electron transfer - Liming Zhang; Jiawei Xie; Yebin Lu; Lingwei Kong; Lei Zhou; Shuangqi Wu; Weicong Wang; Jianshi Huang; Jianfeng Li; Shuiping Cheng (Bioresource Technology, 2026)

Self-supported cube-like Cu nanoparticles with in-situ growth for efficient CO2 electroreduction to hydrocarbons - Peijun Li; Weicong Xu; Xing Wang; Chao Liu; Anze Ning; Qingwen Chen; WulejiasiI Aerxin; Tao Li; Haowei Huang; Rui Xiao (Journal of Environmental Chemical Engineering, 2026)

Integrating elite selection and micropropagation: a production line for early-stage domestication of Vaccinium bracteatum - Chuizheng Xia; Muhammad Junaid Rao; Ying Wu; Yuanyuan Li; Xuefeng Wang; Weicong Hong; Mengxue Wang; Yihong Jin; Jiani Zhu; Xuan Yu; Haidi Yuan; Jiao Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Functional characterization of the Rab11 and its response to SGIV infection in the orange-spotted grouper (Epinephelus coioides) - Liqun Wang; Haiqing Li; Yanjie Shi; Weicong Li; Wenjie Gao; Deqi Wu; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2026)

A calmodulin-like protein from Kentucky bluegrass PpCML29 confers drought tolerance through activating antioxidant defense to maintain ROS homeostasis - Yihan Su; Yuhui Li; Weicong Luo; Ying Liu; Zhenfei Guo; Shaoyun Lu (Journal of Plant Physiology, 2026)

Dynamic succession and biodegradation potential of microplastic prokaryotic microbial communities in the Pearl River estuary - Weicong Yan; Danling Tang; Manzoor Ahmad; Pandeng Wang; Jialing Li; Ziqi Peng; Wenjun Li (Marine Pollution Bulletin, 2026)

Enhancing urban bird corridor identification by integrating three-dimensional factors: A validation with citizen science data - Yaling Huang; Ziru Chen; Yankai Huang; Tongyan Li; Chengyu Ran; Ying Lin; Yinghong Ding; Deng Pan; Yuxiang Lan; Jiali Jin; Zhipeng Zhu; Weicong Fu (Urban Forestry & Urban Greening, 2026)

Subway station facility layout optimization for efficient evacuation: a hybrid method of adaptable queueing network and heuristic retrieval - Chen Junfeng; Lo Siuming; Zhou Yiqi; Yue Shunyu; Zhong Maohua; Hua Fucai; Li Weicong (Tunnelling and Underground Space Technology, 2026)

A network approach to promoting cold island connectivity for mitigating the urban heat island effect: Key areas and targeted strategies - Yankai Huang; Jingkai Huang; Yaling Huang; Tongyan Li; Chengyu Ran; Jiali Jin; Shuang Zhao; Yuxiang Liu; Weicong Fu (Journal of Environmental Management, 2025)

Mechanisms of Ratoon Sugarcane Nitrogen Accumulation and Yield Formation Under Intercropping with Fenlong Tillage “145” Mode - Weicong Zeng; Jingjing He; Shijian Han; Ruchuan Li; Shili Meng; Chenjie Lan; Zhenli He; Suli Li; Benhui Wei; Zhigang Li (Journal of Soil Science and Plant Nutrition, 2025)

A new way to obtain the weighted mean temperature (Tm): Using the Geostationary Interferometric Infrared Sounder (GIIRS) equipped on FengYun Satellite - Fei Yang; Yue Sun; Mingjia Liu; Shiji Song; Weicong Chen; Zhicai Li; Lei Wang (Atmospheric Research, 2025)

Antibacterial mechanism of atmospheric cold plasma against Pseudomonas fluorescens and Pseudomonas putida and its preservation application on in-packaged red shrimp paste - Jiajie Hu; Yao Zhang; Weicong Pan; Qianyun Han; Yu Wei; Yuwei Li; Yi Hu; Xiaoguo Ying; Andrea Armani; Alessandra Guidi; Shanggui Deng (Food Chemistry, 2025)

Study on the characteristics of bird communities in urban river corridor parks and green spaces - Yinghong Ding; Dulai Zheng; Yuxin Lin; Junyi Li; Weicong Fu; Ziru Chen; Jin Yang; Xiaoling Xu; Zhipeng Zhu (Environment, Development and Sustainability, 2025)

Palladium phosphide interlayer sandwiched into Pd nanocrystals for enhanced formic acid electrooxidation reaction performance - Yangzi Zheng; Jiapeng Huang; Ruiyun Guo; Tianou He; Yanan Li; Yaming Liu; Weicong Wang; Qi Zhan; Shangdong Ji; Mingshang Jin (Chemical Engineering Journal, 2025)

Selective enrichment of high-risk antibiotic resistance genes and priority pathogens in freshwater plastisphere: Unique role of biodegradable microplastics - Fan Wang; Zhixun Hu; Wanjun Wang; Jiaxin Wang; Yongyin Xiao; Jialin Shi; Chao Wang; Weicong Mai; Guiying Li; Taicheng An (Journal of Hazardous Materials, 2024)

Microalgae realizes self N-doped biochar for heavy metal polluted sediment remediation - Weicong Wang; Shuangqi Wu; Jianshi Huang; Xueqi Zhang; Jiawei Xie; Yebin Lu; Jianfeng Li; Jun Wei; Boran Wu; Shuiping Cheng (Journal of Hazardous Materials, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Community structure and carbon metabolism functions of bacterioplankton in the Guangdong coastal zone - Ziqi Peng; Pandeng Wang; Xiaoqing Luo; Qiqi Deng; Ziwen Yang; Jiaxue Wu; Wendong Xian; Weicong Yan; Xiaozhen Mou; Yang Yuan; Wenjun Li; Jialing Li (Marine Life Science & Technology, 2024)
Coastal ecosystems are an important region for biogeochemical cycling, are a hotspot of anthropogenic disturbance and play a crucial role in global carbon cycling through the metabolic activities of bacterioplankton. Bacterioplankton can be broadly classified into two lifestyles: free-living (FL) and particle-attached (PA). However, how coastal bacterioplankton the community structure, co-occurrence networks and carbon metabolic functions with different lifestyles are differentiated is still largely unknown. Understanding these processes is necessary to better determine the contributions of coastal bacterioplankton to carbon cycling. Here, the characteristics of community structure and carbon metabolism function of bacterioplankton with two lifestyles in the coastal areas of Guangdong Province were investigated using amplicon sequencing, metagenomic, and metatranscriptomic techniques. The results show that the main bacterioplankton responsible for carbon metabolism were the Pseudomonadota , Bacteroidota , and Actinomycetota . The microbial community structure, carbon metabolic function, and environmental preferences differ between different lifestyles. FL and PA bacteria exhibited higher carbon fixation and degradation potentials, respectively. A range of environmental factors, such as dissolved oxygen, pH, and temperature, were associated with the community structure and carbon metabolic functions of the bacterioplankton. Human activities, such as nutrient discharge, may affect the distribution of functional genes and enhance the carbon degradation functions of bacterioplankton. In conclusion, this study increased the understanding of the role of microorganisms in regulating carbon export in coastal ecosystems with intense human activity.

Effects of Rewilding Aquaculture Time on Nutritional Quality and Flavor Characteristics of Grass Carp (Ctenopharyngodon idellus) - Qianyun Han; Jiajie Hu; Weicong Pan; Jin Yu; Xiaoguo Ying; Jinpeng Weng; Weiye Li; Xudong Weng (Fishes, 2024)
Wild fish are preferred by consumers primarily for their superior sensorial qualities, including taste and texture. However, their limited availability often results in higher prices. Considering this, we explored the possibility of enhancing the quality of earthen pond aquaculture fish by transferring them to a near wild environment. This study investigated how rewilding time affects the physical properties, nutritional composition, and volatile profile of grass carp muscle. The results showed that compared to the 0M group, the crude protein content in grass carp muscle did not change significantly (p > 0.05) as the rewilding time increased to 6 months. Meanwhile, the significant increase in hardness and springiness (p

Experimental investigation on boiling heat transfer characteristics of R1234yf/R1336mzz(Z) in horizontal flow - Mengtao Liu; Li Guo; Wei Li; Weicong Xu; Li Zhao (International Journal of Refrigeration, 2024)

Experimental analysis of boron dilution transient flow mixing characteristics based on planar laser induced fluorescence measurement - Weicong Zhu; Dongyang Li; Mingpeng Chen; Guanhui Xie; Sichao Tan; Ruifeng Tian (Annals of Nuclear Energy, 2024)

Surface reconstruction of copper foil via electrochemical etching to proliferate CH4 production from CO2 electroreduction - Weicong Xu; Chao Liu; Peijun Li; Hongyun Zeng; Xianjun Lu; Xinyu Li; Tao Li; Rui Xiao (Journal of Cleaner Production, 2023)

Real-time recombinase-aided amplification assay for rapid amplification of the IS1081 gene of Mycobacterium tuberculosis - Yuanyuan Liu; Weicong Ren; Zhongtan Xue; Yuedong Miao; Wei Wang; Xuxia Zhang; Cong Yao; Yuanyuan Shang; Shanshan Li; Fengling Mi; Yu Pang (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Hypoxia formation triggered by the organic matter from subsurface chlorophyll maximum in a large estuary-shelf system - Dou Li; Jianping Gan; Zhongming Lu; Weicong Cheng; Hiusuet Kung; Junlu Li (Water Research, 2023)

Methods and experiments for collecting information and constructing models of bottom-layer contours in paddy fields - Tuanpeng Tu; Jie He; Xiwen Luo; Lian Hu; Pei Wang; Gaolong Chen; Li Tian; Dawen Feng; Zhimin Wang; Zhongxian Man; Weicong Li; Zhenghui Wei; et al. (Computers and Electronics in Agriculture, 2023)

Transformation of coccolithophorid Emiliania huxleyi harboring a marine virus (Coccolithoviruses) serine palmitoyltransferase (SPT) gene by electroporation - Weicong Cai; Xueting Wang; Jinjing Su; Jian Li; Jun Zeng; Guiling Li; Jingwen Liu (Journal of Oceanology and Limnology, 2021)

Virus-induced apoptosis and phosphorylation form of metacaspase in the marine coccolithophorid Emiliania huxleyi - Jingwen Liu; Weicong Cai; Xian Fang; Xueting Wang; Guiling Li (Archives of Microbiology, 2018)